Preferential solvation of the antioxidant agent daidzein in some aqueous co-solvent mixtures according to IKBI and QLQC methods (2015)
The preferential solvation parameters by ethanol (EtOH) or propylene glycol (PG) of daidzein were derived from their solution thermodynamic properties by means of the inverse Kirkwood-Buff integrals and the quasi-latticequasi- chemical (QLQC) methods. According to IKBI method, the preferential solvation parameter by the co-solvent, x1,3, is negative in water-rich mixtures but positive in co-solvent-rich mixtures in both kinds of systems. This could demonstrate the relevant role of hydrophobic hydration around the aromatic rings in the drug solvation in water-rich mixtures. Furthermore, the more solvation by co-solvent in co-solvent-rich mixtures could be due mainly to polarity effects and acidic behavior of the hydroxyl groups of the compound in front to the more basic solvents present in the mixtures, i.e. EtOH or PG. Otherwise, according to QLQC method, this drug is preferentially solvated by the co-solvents in all the mixtures in both kind of systems.